Biomineralization of Enamel and Dentin Mediated by Matrix Proteins. (September 2021) - Moradian-Oldak, J.; George, A.
Biomineralization of enamel, dentin, and bone involves the deposition of apatite mineral crystals within an organic matrix. Bone and teeth are classic examples of biomaterials with unique biomechanical properties that are crucial to their function. The collagen-based apatite mineralization and the important function of noncollagenous proteins are similar in dentin and bone; however, enamel is formed in a unique amelogenin-containing protein matrix. While the structure and organic composition of enamel are different from those of dentin and bone, the principal molecular mechanisms of protein–protein interactions, protein self-assembly, and control of crystallization events by the organic matrix are common among these apatite-containing tissues. This review briefly summarizes enamel and dentin matrix components and their interactions with other extracellular matrix components and calcium ions in mediating the mineralization process. We highlight the crystallization events that are controlled by the protein matrix and their interactions in the extracellular matrix during enamel and dentin biomineralization. Strategies for peptide-inspired biomimetic growth of tooth enamel and bioinspired mineralization of collagen to stimulate repair of demineralized dentin and bone tissue engineering are also addressed.